“A Sort of Refusal”: Alice Munro’s Reluctant Career - York, Lorraine (Studies in Canadian Literature / Études en littérature canadienne, 2016)
This essay considers how celebrity reluctance operates in the Canadian literary field, using Alice Munro’s career, reception, consecration, and fiction as an example of how reluctance as a public feeling negotiates the literary marketplace, how it works in the national imaginary to legitimize model Canadian subjects, and how it operates globally, as an implicit critique of a neoliberal economic order that places a premium on moving forward. In examining the celebrity of Alice Munro, the essay remains attentive to the way in which her reluctant consecration on the global stage, most clearly figured in her humble reception of the Nobel Prize for Literature, operates on both national and international registers, as an example of what Laura Moss has called “transnational-nationalism”: the production of Canadian culture for a global audience and, concomitantly, a reflection of that global stardom back onto specifically Canadian debates about national culture, character, and prestige. In keeping with Richard Dyer’s definition of the “star image” as an “extensive, multimedia, intertextual layered accretion” that “consists of everything that is publicly available” about the star, this analysis places media representations of Alice Munro and her career alongside Munro’s own fictional representations of reluctance.